Ecological consequences of genetic variation in foraging behaviors of a predatory mite - Nachappa, Punya (Kansas State University, 2008)
Foraging traits such as prey consumption rate and the efficiency with which predators convert their prey into offspring are important determinants of local predator-prey dynamics. However, in environments with patchy prey distribution, predator dispersal and aggregation in response to prey-induced volatile cues becomes more critical. My dissertation addressed predator-prey population dynamics in response to variation in four foraging traits in the predatory mite, Phytoseiulus persimilis (Acari: Phytoseiidae): consumption rate, conversion efficiency, dispersal, and olfactory response related to prey. The dispersal response and olfactory sensitivity in predatory mites is modified by prey-related cues. For example, the dispersal response increased with decreasing prey density in a patch and increasing prey-related volatiles from outside the prey patch. The olfactory response of predatory mites also increased with increasing numbers of prey per plant or with the length of time a plant was infested by prey. These results formed the basis for development of bioassays used to examine genetic variation in dispersal and olfactory response of predatory mites. Through artificial selection I documented additive genetic variation in all four traits. After relaxation of selection, high-level phenotypes were stable compared to their low counterparts. There were significant genetic correlations between some of the foraging traits. However, there were no correlations between foraging traits and life-history traits. The existence of genetic variation and covariation among the foraging traits suggests that predatory mites must be able to adopt different foraging strategies in the evolution of prey-finding in a tritrophic system. High consumption, high conversion efficiency and high dispersal response phenotypes interacted differently with prey in a spatially complex landscape. All foraging traits were comparable in terms of predator-prey densities and plant damage; but they were lower than the unselected control. Spatial association and correlation analysis showed that all foraging traits were positively associated with prey; but the strongest association was observed for the high conversion efficiency and dispersal lines. The variability in foraging behaviors of the predatory mite affects its ability to locate patchily distributed prey, thereby influencing foraging efficiency and population dynamics. This research provides new information about the critical link between predator foraging and population dynamics relevant to biological control.
Keywords: Predatory mite; Spider mite; Foraging behavior; Biological control; Biology, Entomology (0353); Biology, Genetics (0369)